Model Pembelajaran Berbasis Proyek Dalam Meningkatkan Kreativitas Siswa Sekolah Dasar - Farras Nabiha Atilla; Nurhafizah Asih; Gusmanel (GLOBAL SCIENTS PUBLISHER, 2025)
The Project-Based Learning (PjBL) model is an approach that emphasizes the active involvement of students in producing tangible products through project completion stages. The purpose of this study was to determine the implementation of PjBL in elementary schools and its impact on student creativity, as well as to identify supporting and inhibiting factors. Furthermore, this study compared the creativity of students learning through PjBL with students learning using conventional methods. The results indicate that PjBL is able to create meaningful learning because students gain direct experience in exploring ideas and solving problems. Student creativity increases through activities such as designing, collaborating, documenting, and documenting project results. Factors supporting the effectiveness of PjBL include teacher competence, infrastructure, and student motivation. While the main obstacles are time constraints and differences in student abilities within groups. A comparison between the experimental and control classes revealed significant differences, with the class implementing PjBL achieving greater increases in creativity. Therefore, PjBL is recommended as a relevant learning method for developing student creativity in line with the demands of 21st-century education.